2009
DOI: 10.3109/17453670903025345
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate after limb deformity correction by the Ilizarov method with or without knee joint distraction

Abstract: Background and purpose Growth inhibition and stimulation have both been reported after juvenile limb lengthening. Distraction of a joint usually suspends and unloads the growth plate and may stimulate growth. We investigated the influence of knee joint distraction on the speed of growth after limb lengthening.Methods In a retrospective study, growth patterns were analyzed in 30 children mean 61 (24–109) months after limb lengthening with the Ilizarov method, each child having more than 2 years of remaining gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
1
0
1
Order By: Relevance
“…The stimulatory effect when lengthening was performed under optimal conditions was found to reach up to 5% of the final lengthened segment. Some authors have found no change in growth rate in older patients [17,21,24,46], although some authors have found stimulatory effects in young patients despite a higher mean percent lengthening [38]. In our study, using preoperative and postoperative measurements of developmental femoral and overall length discrepancies matched the findings of Popkov et al and others, showing no detrimental effect on femoral growth in young patients who underwent a relative femoral lengthening greater than 23.5% [17,21,45].…”
Section: Discussionsupporting
confidence: 84%
“…The stimulatory effect when lengthening was performed under optimal conditions was found to reach up to 5% of the final lengthened segment. Some authors have found no change in growth rate in older patients [17,21,24,46], although some authors have found stimulatory effects in young patients despite a higher mean percent lengthening [38]. In our study, using preoperative and postoperative measurements of developmental femoral and overall length discrepancies matched the findings of Popkov et al and others, showing no detrimental effect on femoral growth in young patients who underwent a relative femoral lengthening greater than 23.5% [17,21,45].…”
Section: Discussionsupporting
confidence: 84%
“…The harmful effects of hyper-pressure on cartilage tissue, impaired vascularisation and shaft ischaemia may account for the subsequent slowdown in growth. Oostenbroek et al recommended bridging the knee in order to obtain a subsequent stimulation in growth [19, 20], but we did not observe any statistically significant modification in residual growth in the knee joint distractions performed. On the other hand, knee distraction avoids joint contracture and dislocation.…”
Section: Discussioncontrasting
confidence: 77%